Private Speech as Social Action. (30th July 2015) - Hauser, Eric
Abstract : An important theoretical construct within the Vygotskian sociocultural approach to second language learning is private speech. Within a conversation-analytic framework, an agnostic stance is taken in this paper toward the possible intrapsychological function(s) of private speech in order to (1) illustrate how private speech can be identified within the details of talk-in-interaction and (2) how private speech can be understood as social action. It is argued that attention to the details of how private speech is produced is important in order to show how private speech has been identified as such; that viewing private speech as social action allows for a more emic perspective; and that, at least within interaction, private speech is social not just in origin, but each time that it is produced.